Financial Inclusion and Human Development in India: An Inter-State Analysis - Meenu Kumari (International Journal of Economics Development Research (IJEDR), 2022)
This paper investigates whether financial inclusion contributes to economic development in India. This research paper was based on secondary data. The period of the study is 2019. In this paper, we are analysing the situation of financial inclusion in 28 states of India. The results suggest that the level of financial inclusion is very poor in most of the states and further analysis points a direct relation of financial inclusion with growth and standard of living while a negative relation with poverty. As a result of the work, we found that there is a positive correlation between financial inclusion and human development, demonstrated in the Pearson correlation matrix. Therefore, financial inclusion is an important drive for economic development, promoted through the access and use of formal financial systems, and it contributes in human development. Further, it contributes in economic development in India.